Associação dos polimorfismos genéticos da desidrogenase de glicose 6-Fosfato e antígenos DUFFY na malária vivax e mutações de G6PD em doadores de sangue - Ferreira, Natalia Santos (2019)
Malaria is the most representative parasitic disease in the world. However, in Brazil, P. vivax represents the most prevalent species, especially in the Amazon region, where several clinics have shown greater severity, especially in cases of severe anemia. Some studies have reported a high prevalence of the Duffy FYA and FYB alleles among patients with falciparum and vivax malaria, while other genotypes found have been associated with decreased infection rates. The induction of hemolysis due to glucose-6-phosphate dehydrogenase (G6PD) deficiency by the use of antimalarial drugs has added studies in endemic areas correlated with the high prevalence of G6PD deficiency. This study aims to evaluate the association of synergism between G6PD polymorphisms and Duffy antigens in patients with vivax malaria in the state of Amazonas. The characterization of G6PD was performed using the real-time PCR technique, whereas for Duffy antigens they were genotyped by PCR-RFLP. Molecular genotyping was performed in 225 patients with severe and non-severe vivax malaria, and in 1,200 blood donors from Amazonas. Among malaria patients, 12.94% had SNP G202A and 19.19% had A376G. And for Duffy Phenotypes, 31.11% (a+b-), 43.55% (a+b+), 24.9% (a-b+) and 0.44% (a-b-) were identified. The FYA / FYB genotype was more frequent among patients. In addition, the G202A / A376G genotypes showed a higher frequency in severe malaria, being for c.202 (RR = 5.57 - p <0.001) and for A376G (RR: 4.49 - p <0.001) strongly associated with previous episodes of malaria (p <0.001). We also found a frequency of 8.27% of the G6PD polymorphism among blood donors from the Hematology and Hemotherapy Foundation of Amazonas in blood donors. Additional research for deficiency of G6PD and Duffy antigens would be valuable, especially focused on areas of high population density. We conclude that SNPs G202A and A376G were risk factors for the development of severe vivax malaria and that molecular diagnosis before treatment may be necessary in the Amazonian population